Radiological Features of Paraquat Herbicide Poisoning: A Case Report - Agin, Khosrow; Shadnia, Shahin; Mostafazadeh, Babak (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Paraquat (PQ) is a herbicide with potent toxicity. The most frequent human poisoning occurs by ingestion and inhalation. Its clinical feature includes pulmonary edema in the first 48 hours post-toxicity with progression to acute respiratory distress syndrome. A 50-year-old male poisoned patient referred to the emergency department with the complaint of shortness of breath. His companions had an herbicide poison bottle. Respiratory failure gradually intensified. The patient was intubated and under mechanical ventilation for one month. kidney and liver insufficiency were gradually added to the patient’s clinical feature in the following days. He died with multiorgan failures one month later. Standard chest X-ray is not beneficial for assessing PQ intoxication. High resolution computed tomography scan is recommended at day 7 post-ingestion for evaluating PQ poisoning.